Prisoner Reintegration in Hungary, with Special Regard to the Freedom of Religious Practice - Pintér, Bálint; Nagy, Anita (International Journal of Criminology and Sociology, 2026)
This study aims to demonstrate that persons convicted and serving their sentence in a penal institution in Hungary are afforded the opportunity to exercise and live out their religion. The realization of this right is supported by an assortment of instruments and institutional arrangements; among these, the role of a prison chaplain being of particular and noteworthy significance. Overall, these mechanisms may contribute, not only to the effective enjoyment of freedom of religion and the practical opportunity of religious observance, but also to successful reintegration—namely, enabling a convicted person to re-enter and participate in the general community as a full member of society, and to be free from any stigma or undue labelling because of their past.